Ball and beam system control using PID-based ANFIS controllers. (2016) - Kharola, Ashwani; Patil, Pravin
This paper presents a MATLAB/Simulink-based offline control of highly nonlinear, multivariable and complex ball and beam system. The objective is to control both beam orientation and ball position using PID-based ANFIS controllers. The simulation results of PID controller were used for training of ANFIS controller. The FIS for ANFIS controller were designed using three gbell membership functions. The simulation results of PID-based ANFIS controller showed excellent learning ability and control of ball and beam system as compared to conventional PID controller.